2006
DOI: 10.1073/pnas.0602844103
|View full text |Cite
|
Sign up to set email alerts
|

The callipyge mutation enhances bidirectional long-range DLK1-GTL2 intergenic transcription in cis

Abstract: The callipyge mutation (CLPG) is an A to G transition that affects a muscle-specific long-range control element located in the middle of the 90-kb DLK1-GTL2 intergenic (IG) region. It causes ectopic expression of a 327-kb cluster of imprinted genes in skeletal muscle, resulting in the callipyge muscular hypertrophy and its non-Mendelian inheritance pattern known as polar overdominance. We herein demonstrate that the CLPG mutation alters the muscular epigenotype of the DLK1-GTL2 IG region in cis, including hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
(34 reference statements)
1
38
0
Order By: Relevance
“…This element is located 9136 bp upstream from a conserved dodecamer motif that contains a single nucleotide polymorphism causing the Callipyge phenotype in sheep (29,33). Interestingly, the Callipyge mutation was recently shown to enhance bidirectional long range Dlk1-Gtl2 intergenic transcription in cis (25). Therefore, because the novel MAR4 activity appears to be stronger when the MAR4 is inserted in the antisense direction (with respect to the endogenous locus) in a reporter construct, its action may potentially favor transcription of antisense transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…This element is located 9136 bp upstream from a conserved dodecamer motif that contains a single nucleotide polymorphism causing the Callipyge phenotype in sheep (29,33). Interestingly, the Callipyge mutation was recently shown to enhance bidirectional long range Dlk1-Gtl2 intergenic transcription in cis (25). Therefore, because the novel MAR4 activity appears to be stronger when the MAR4 is inserted in the antisense direction (with respect to the endogenous locus) in a reporter construct, its action may potentially favor transcription of antisense transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Georgiades et al (40) found strong evidence for imprinting on chromosome 12, especially at the telomeric end of the chromosome where the genes involved in the callipyge mutation occur (33,38,39). However, Bwi12.1 maps proximal to the known imprinted region so it seems to represent a unique imprinting region, although imprinting has been implicated in the effects of a mutation (Adp) caused by a transgene insertion into the region of Bwi12.1 (40, 41).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic molecular events of this genetic process include paternal overexpression of DLK1 and PEG11/RTL1 and normal maternal expression of Gtl2, Rian, antiPeg11, and miRs (19). The prevalent working model for polar overdominance predicts that maternal noncoding RNA within the Dlk1-Dio3 imprinting region may serve as a trans-regulator of DLK1 expression, thereby causing the CLPG phenotype (4).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed a point mutation (A to G transition) within the intergenic region between the Dlk1 and Gtl2 genes of the imprinted Dlk1-Dio3 region (17,18), which affects a muscle-specific, long-range cis-acting control element (18). The point mutation in the paternal allele up-regulates the transcription of genes including Dlk1 and Peg11 in cis without altering the imprinting status (19). When this mutation occurs in the maternal allele, it up-regulates the expression of noncoding RNAs in the Dlk1-Dio3 region.…”
mentioning
confidence: 99%